Comparison of Self-Management between Glycemic Controlled and Uncontrolled Type -2 Diabetic Elderly in Thailand: A Qualitative Study - P. Wongrith; P. Thiraratanasunthon; S. Kaewsawat; C. N. Le (Сахарный диабет)
BACKGROUND: For the past few decades, there have not been many studies done regarding diabetic patients’ perspectives. Diabetes mellitus is serious long-term care required for older patients. The facilitators have an important role in supporting diabetes patients.AIM: The study aimed to assess and compare patients’ and caregivers’ perception of diabetes self-monitoring (DSM) and affects the Diabetes Self-Management Instrument (DSMI) of type-2 diabetic patients in both glycemic controlled and uncontrolled patients.MATERIALS AND METHODS: The descriptive cross-sectional qualitative method was used to gather data from 25 participants among type II diabetes patients. Patients were recruited from the outpatient diabetes clinics in southern Thailand. Data were collected using a semi-structured in-depth interview guide and the focus group discussion. A thematic analysis approach was used to process the data.RESULTS: From this study, 60% of the participants were among the uncontrolled glycemic group while 40% were the controlled group. The controlled group was found to have better self-management in the five themes of a healthy diet, regular exercise, medication taking, and risk prevention than the uncontrolled group. T2DM elderly in a controlled group has self-awareness and diabetic management intention higher than the uncontrolled group. The patient’s attitudes revealed five themes described fours themes of diabetic self-management intentions as reasoning, deciding, acting, and evaluating to perform self-management of older T2DM patients.CONCLUSION: The elderly T2DM in the glycemic control group had self-awareness and intended to manage their diabetes and received more family support than those who were unable to control their blood sugar levels. Perceptions of elderly diabetic patients, their caregivers, and health workers revealed a common concern for behavioral intentions: obtaining self-care support from healthcare professionals and their families were the most important aspect of glycemic control in the elderly.